1984
DOI: 10.1177/109114218401200202
|View full text |Cite
|
Sign up to set email alerts
|

State Income Tax Progressivity

Abstract: This article compares the degree of personal income tax progressivity in selected states and investigates the determinants of changes in progressivity through time. D. Suits's and N. C. Kakwani's recently proposed summary measures of tax progressivity are estimated and compared for twelve states with comparable income tax systems. Time series estimates are made for a single state, North Carolina. The analysis reveals that there are systematic differences in progressivity among the states and that inflation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Formby and Sykes, 1984). Second, state and local taxes make up a much smaller share of the American revenue structure than consumption taxes make up of the European revenue structure (Carey and Rabesona, 2002).…”
Section: Literature Review and Data Sourcesmentioning
confidence: 99%
“…Formby and Sykes, 1984). Second, state and local taxes make up a much smaller share of the American revenue structure than consumption taxes make up of the European revenue structure (Carey and Rabesona, 2002).…”
Section: Literature Review and Data Sourcesmentioning
confidence: 99%
“…As discussed earlier, interpretation of global measures may need to be supplemented by local measures and comparison of Lorenz curves (Baum 1998;Formby and Sykes 1984).…”
Section: Discussionmentioning
confidence: 99%
“…In times of rising incomes, M-T may move differently from S and K depending on whether yield effects or the 'compressing' effects of income inflation on the distribution of tax liabilities dominate the rise in tax liabilities. 8 Empirical studies for North America have shown that the three tax progressivity indices will also not necessarily move in the same direction as the distribution of income varies (Formby, Seaks and James-Smith 1981;Formby and Sykes 1984). For example, the M-T index may move in the same direction as the K index if tax yield is constant, but not necessarily the same as the S index.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations